Anatomiye Güncel Bakış II - Aygün, Tayfun; Yücel, Nurullah; Seçgin, Yusuf; Öner, Zülal; Bakıcı, Rukiye Sümeyye; Şahin, Necati Emre; Aksu, Feyza; Aras, Onur; Akkoç, Ramazan Fazıl; Kösetürk, Taner; Bedre Duygu, Özden; Durmaz, Sevda Canbay; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-